The Development of Flipbook-based E-module with “FAMILIE” Theme for Students of 11st Grade SMA - Novie Catur Wahyuningtyas; Rosyidah Rosyidah (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
The objective of this study is to develop e-module teaching material based on flipbook with the topic of “Familie”.This study is quantitative and qualitative research with an instrument of questionnaire. Based on the validation results, the e-module was rated 89% by media expert and 92% by the material expert. Assessment from the expert teams was included in very valid category. In addition, assessment of students to flipbook e-module obtained average score of 89% with very good criteria. Based on the results of research then it can be concluded that e-module based on flipbook is feasible to be used as an independent teaching material by students of 11th SMAN 1 Gondanglegi. E-module based on flipbook is very interesting and easy to used to help students in the learning process.